P04.62 The oncometabolite R-2-Hydroxyglutarate suppresses the innate immune microenvironment of IDH1-mutated gliomas via aryl hydrocarbon receptor signaling. (19th September 2018) - Friedrich, M; Bunse, L; Bunse, T; Green, E; Kessler, T; Pusch, S; Sanghvi, K; Carretero, R; Gutcher, I; von Deimling, A; Wick, W; Platten, M
Abstract: Background: IDH1-mutated gliomas are associated with less abundant and phenotypically skewed innate and adaptive immune cell infiltrates compared to IDH1 wild-type tumors. Despite this, the most frequent mutation - IDH1R132H - represents a clonal shared neoantigen and mutations in IDH are associated with a more favorable prognosis. While the tumor cell-intrinsic consequences of the oncometabolite R-2-hydroxyglutarate (R-2-HG) accumulating in IDH1-mutated gliomas as a result of a neomorphic enzymatic function, are well-characterized, potential direct paracrine effects of R-2-HG influencing the glioma immune microenvironment remain incompletely understood. Aim: This study aimed at characterizing the impact of the oncometabolite R-2-HG on the innate immune microenvironment of IDH1-mutated gliomas. Methods and Results: By means of comprehensive analyses of expression datasets from human gliomas and syngeneic murine tumor models as well as transporter studies we demonstrate that R-2-HG is imported by both microglia and macrophages via SLC family transporters and suppresses their function in a paracrine manner. Functional analyses of microglia and macrophages indicate an R-2-HG-driven induction of tolerogenicity as evidenced by accumulation of IL10 and TGFβ and suppression of MHC-II expression, which results in impaired activation of antigen-specific T cells and activation of immune checkpoint molecules. Multi-level signature profiling of human tumor-infiltrating as well as primary immune cells was complemented by reporter gene assays and pathway analyses and revealed that R-2-HG activates the cytosolic transcription factor aryl hydrocarbon receptor (AHR), a key immunomodulatory target of immunosuppressive tryptophan metabolism. By means of knockout models, the observed immunosuppressive phenotype was shown to be AHR-dependent. Functional relevance of R-2-HG-mediated, AHR-driven impairment of myeloid cell immunity was demonstrated in vivo by pharmacological AHR inhibition, increasing the efficacy of checkpoint blockade. Conclusion: R-2-HG impairs antitumor immunity in IDH1-mutated gliomas by activating the AHR in innate immune cells, thus suppressing the innate immune microenvironment by compromising antigen presentation and activation of antigen-specific T cells. This, together with recent findings on inhibitory effects on T cell immunity, represents a novel mechanism of immune evasion of an immunogenic driver mutation and opens a novel therapeutic approach to IDH1-mutated gliomas.